Information support of operative-search activity on struggle against criminal offenses in the field of production and sale of alcoholic beverages - Lysenko, Andrii; Lysenko, Iryna (Centre for European Reforms Studies, 2021)
A significant factor influencing the timely and effective detection of criminal offenses, including in the production and sale of alcoholic beverages, is the proper organization of work on information support of operational and investigative activities, which includes: acquisition and location of various sources of information, informatization of all areas of work on the fight against crime, the creation of information systems, the use of modern technical means, high-speed systems for receiving and transmitting both general and operational information, and their processing, etc. Without a well-established and functioning system of information support for operational and investigative activities, adequate counteraction to crime is problematic. Given the above, this scientific work is devoted to the organization of information support of operational and investigative activities to combat criminal offenses in the field of production and sale of alcoholic beverages and solving related problems.
Keywords: operative-search activity; information-analytical support; information; criminal offenses; sphere of production and sale of alcoholic beverages